Awareness, trust, and adoption of blockchain technology and cryptocurrency among blockchain communities in Malaysia - Ku-Mahamud, Ku Ruhana; Omar, Mazni; Abu Bakar, Nur Azzah; Muraina, Ishola Dada (Insight Society, 2019)
Blockchain technology and cryptocurrency are attracting increasing attention from consumers, investors, investment industry and regulators. Cryptocurrency has great potential to be used for transaction or investment in the future. However, level of awareness of the blockchain technology and cryptocurrency is still at infant stage, specifically in developing countries. Thus, this study aims to investigate the level of awareness, trust and adoption of blockchain technology among blockchain community in Malaysia. Quantitative approach was adopted in this study where a new questionnaire was developed in the first phase to measure the level of awareness, adoption, and trust of blockchain technology applications among Malaysian blockchain communities. The resulting questionnaire consists of items on respondents’ demographic, their awareness, trust, and adoption of FinTech particularly on blockchain technology and cryptocurrency. In the second phase, a pilot study was conducted to validated the new questionnaire from 304 respondents. Reliability test using Cronbach’s alpha with a value of 0.908. A real survey was also conducted in this phase using the validated queationnaire and data were obtained online from 304 respondents. Descriptive statistics were used in the analysis during the third phase of the study, and results demonstrate that the awareness level of blockchain technology and cryptocurrency are at the intermediate level. Nevertheless, the majority of respondents are confident and trust that the blockchain technology can offer a stable and secure platform, which gives positive impact on the application of the technology. Empirical results provide significant insights into the development of the blockchain technology industry in the country.